LDPE cracking over mono- and divalent metal-doped beta zeolites. Issue 13 (17th May 2022) - Kokuryo, Shinya; Tamura, Kazuya; Miyake, Koji; Uchida, Yoshiaki; Mizusawa, Atsushi; Kubo, Tadashi; Nishiyama, Norikazu
Abstract : This study evaluates the effect of loading various mono and divalent metals in Beta zeolite on low-density polyethylene (LDPE) cracking. We revealed that Tl and Ba ions enhanced Lewis acidity, leading to higher catalytic activity on LDPE cracking. Abstract : This study investigated the catalytic activity on low-density polyethylene (LDPE) cracking over metal-doped beta zeolites. We prepared beta zeolites loaded with various metal cations by an impregnation method. Tl- and Ba-loaded beta zeolites showed higher catalytic activity than a pristine beta zeolite. To specify the chemical species that promote catalytic degradation of LDPE, we also prepared Tl and Ba ion-exchanged zeolites. The Tl and Ba ion-exchanged zeolites showed similar catalytic activity to Tl- and Ba-loaded beta zeolites prepared by an impregnation method, suggesting that the Tl and Ba ions on the zeolite frameworks are active species for LDPE cracking. Our characterization revealed that the Tl and Ba ions enhanced the Lewis acidity, leading to their higher catalytic activity on LDPE cracking. Moreover, we revealed that an excess amount of Tl and Ba formed bulk aggregated species that show almost no degradation activity. This work provides clear and informative guidelines for the catalyst design on polymer cracking.